Superfícies Seletivas em frequência Complementares (CFSS): conceito e projeto - Silva, Bruno Sátiro da (2018)
Wireless communications are an integral part of modern society, with fundamental role in the process of globalization and technological progress. Therefore, several researches are carried out in order to achieve constant optimization in this area. Frequency Selective Surfaces (FSS) have been approached for decades because of its telecommunications functionalities. Due to evolution of technology, new demands arise every day, each one with specific responses for each application, thus, the FSS need to be modeled to meet the most diverse requirements. In this context, the present work aims to show a specific model of FSS. The Complementary Frequency Selective Surfaces (CFSS) have very interesting characteristics for modern communication systems, such as multi-band frequency behavior, high selectivity in transmission bands, narrow null bands and great angular stability, being useful in a wide range of applications, such as aircrafts, radomes and satellite communication. As part of this work, new unit-cell geometries for CFSS were proposed and analyzed. Computational simulations, with a detailed parametric study of the proposed structures, were performed for a better understanding of the frequency response.